2004
DOI: 10.1103/physrevlett.92.026808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quantum Confinement on the Dielectric Function of PbSe

Abstract: Monolayers of lead selenide nanocrystals of a few nanometers in height have been made by electrodeposition on a Au(111) substrate. These layers show a thickness-dependent dielectric function, which was determined using spectroscopic ellipsometry. The experimental results are compared with electronic structure calculations of the imaginary part of the dielectric function of PbSe nanocrystals. We demonstrate that the size-dependent variation of the dielectric function is affected by quantum confinement at well-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 11 publications
3
37
0
Order By: Relevance
“…Fig. 39(b) compares the 3 nano-Si derived herein and other sophisticated calculations of nanosolid Si and the third-order dielectric susceptibility of Ag nanodots [605]. Although the dielectric susceptibility does not follow the BOLS prediction, it shows the suppressed trend.…”
Section: Dielectric Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 39(b) compares the 3 nano-Si derived herein and other sophisticated calculations of nanosolid Si and the third-order dielectric susceptibility of Ag nanodots [605]. Although the dielectric susceptibility does not follow the BOLS prediction, it shows the suppressed trend.…”
Section: Dielectric Suppressionmentioning
confidence: 99%
“…Delerue et al [605] deposited PbSe nanocrystals of several nanometers in height on an Au(111) substrate and measured the thickness-dependent dielectric function. Compared with electronic structure calculations of the imaginary part of the dielectric function of PbSe nanocrystals they suggested that the size-dependent variation of the dielectric function is affected by quantum confinement at well-identifiable points in the Brillouin zone, instead of the bandegap transition.…”
Section: Introductionmentioning
confidence: 99%
“…Their use of this modelling approach can be followed back to early work on thin (few nm) crystalline PbSe films [124] where it was used to interpret the appearance of film thickness dependent confinement related features in the dielectric function determined by spectroscopic ellipsometry. The same modelling methods were used to derive a comparison between the tight binding theoretical density of states and the density of states function derived from STM measurements on 3 and 7 nm diameter PbSe colloidal QDs [125].…”
Section: Modelling the Electronic Structure Of Hgte Nanoparticlesmentioning
confidence: 99%
“…In the literature there is evidence that quantumconfinement effects play an important role throughout the entire Brillouin zone (up to 4 eV) and also influences the dielectric response (and thus n and k) in the high-energy region. [3,4] It will be interesting to see if the analysis of more …”
mentioning
confidence: 99%
“…The analysis by Moreels and Hens shows that a satisfactory agreement in the high-energy region (E 2 in their Figure 3) is obtained by using the wavelengthdependent values for n and k from bulk PbSe. Whether or not the high-energy transitions in PbSe QDs are affected by quantum confinement, if n and k are identical to the bulk values of PbSe in this high-energy region, [3][4][5] and also how to correctly correct for local field effects, [6][7][8] remain important questions. In the literature there is evidence that quantumconfinement effects play an important role throughout the entire Brillouin zone (up to 4 eV) and also influences the dielectric response (and thus n and k) in the high-energy region.…”
mentioning
confidence: 99%